Hollywood hustle : a thriller - Lindstrom, Jon, 1957- (Crooked Lane, 2024)
"Discovering that his troubled adult daughter has been kidnapped, a washed-up movie star with no money to pay the ransom turns to his closest friends, a legendary Hollywood stunt man and a disgraced former LAPD detective, to get her back"--